A Comparison of Squatting Exercise on a Centrifuge and With Earth Gravity - Piotrowski, Timothy; Rittweger, Jörn; Zange, Jochen (Frontiers in Physiology, 2018)
Purpose: Long-duration space missions require countermeasures against the muscular wasting and cardiovascular deconditioning associated with microgravity. Replacing gravitational acceleration by means of centrifugation is a promising alternative as it challenges all physiological systems at once. The aim of this study is to examine the metabolic energy costs of squatting on a centrifuge in comparison with squatting in an upright standing posture under natural gravity. Methods: 24 subjects (11 male, 13 female) performed continuous squatting exercise for 9 minutes with increasing cadence (10, 12, 15 squatsmin-1). This was done in three conditions: Upright under natural gravity and lying supine on a centrifuge at two radii (2.5 and 3.5 m) at 1 g of centrifugal acceleration. Results: Generally, subjects did not suffer from motion sickness. Exercise under natural gravity led to a higher Δ V’O2/body mass (7.1±2.0, mlmin-1kg-1, mean ± SD,) compared with training on the centrifuge (6.1 ±1.6). Exercise efficiency was also reduced under natural 1g at 28.2 ±1.0 % compared to 40.4 ±1,5 % on the centrifuge. As expected, oxygen consumption increased with increasing cadences. The Coriolis-effect had a negligible impact as there was no significant difference in V’O2 between the two radii. However, during centrifugation and upwards movement the right leg was more loaded than the leg left and vice versa during downwards movement. Conclusions: The lower V’O2 on the centrifuge may be attributed to the unloading of trunk muscles while subjects were lying on the sled, which in the upright condition leaning against a sled are still working to stabilize the torso. Subjects tolerated high rotational rates combined with exercise very well.